(untitled) (Research, Society and Development, 2022)
One form of bullying has been more frequent and has gained space in the media and in the scientific community, virtual bullying, or cyberbullying, which has consequences as serious as the traditional ones. Like bullying, cyberbullying can be seen as a public health issue, as a phenomenon that significantly affects the development of children and adolescents, causing short, medium, and long-term consequences. Therefore, the aim of this paper is to analyze and discuss the aspects of this form of aggression through social media, conceptualizing and differentiating it from traditional bullying, focusing on the psychological consequences of the adolescent in the position of victim of cyber aggression. In effect, a bibliographic research was conducted, without specific date criteria, of exploratory nature, where theoretical and empirical studies of authors/researchers were used, such as: Cortés et al. (2021); Hinduja & Patchin, (2020); De Oliveira (2016), among other authors/researchers who permeate the theme of Cyberbullying, the causes and psycho-emotional consequences of adolescents in the context of virtual aggressions, and the context of violence of the victims. We used the following data platforms: Scielo, PePSIC, BVS, BDTD and Google Scholar. The main results suggest that adolescent victims of cyberbullying are more likely to have suicidal ideas, use chemical substances, and present anxiety and depression problems. The study presents that people involved in cyberbullying have lower indicators of self-esteem. We conclude that there is a need for further studies on the subject in Brazil and also the importance of discussing prevention measures and intervention strategies.